A PROTOCOL FOR THE DETECTION OF GENETIC MARKERS IN SALIVA BY POLYMERASE CHAIN REACTION WITHOUT A NUCLEIC ACID PURIFICATION STEP: EXAMPLES OF SARS-COV-2 AND GAPDH MARKERS - Surya Kannan (18456708) (2021)
Introduction Polymerase chain reaction (PCR)-based diagnostic tests use purifi ed nucleic acids (NAs) from clinical samples. The NAs purifi cation step adds time, cost, and aff ects the quality of testing. The objective of this study was to develop a protocol for direct use of saliva in tests for genetic markers, without purifi cation of nucleic acids. Methods PCR, real-time RT-PCR and isothermal amplifi cation tests were used for direct detection of genetic markers, without purifi cation of nucleic acids. Results We report a protocol for the direct detection of genetic markers in saliva. The protocol is based on a collection of saliva in a solution containing a detergent and ethanol and is compatible with isothermal amplifi cation (LAMP), real-time RT-PCR and RT-PCR. SARS-CoV-2 and GAPDH markers were used as reference markers. We observed that mild detergents allow effi cient detection of external reference and intracellular endogenous markers, while strong detergent, e.g. sodium dodecyl sulfate, inhibited the PCR reaction. Under these conditions, saliva samples can be stored for 24 h at +4°C or –18°C with the preservation of markers. Storage at room temperature led to the deterioration of marker detection. Snap heating of saliva samples at the time of collection, followed by storage at room temperature, provided partial protection. Conclusion The protocol presented in this report describes the collection and storage of saliva for direct detection of genetic markers and is compatible with PCR and LAMP tests. Other Information Published in: Proceedings of the Shevchenko Scientific Society. Medical Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.25040/ntsh2021.01.16